Critical Success Factors for the Growth of Roy Paints Pvt. Ltd: A paint retail store in India. - Mittal, Rohit (2008)
This dissertation investigates various critical factors which Roy Paints needs to consider achieving its objective of growth both in terms of Sales and Number of Showrooms. This report cites references from significant literatures on retailing to determine factors important for the growth of a Retail Store. As understanding customer needs is essential in the development of retail strategies, having an optimal mix of marketing strategies is equally necessary to reach out to different types of customers.